A COMPARATIVE STUDY OF CERULEOPLASMIN OXIDASE WITH COPPER AND RENAL FUNCTION TESTS IN SERA OF LEUKEMIA AND MULTIPLE MYELOMA PATIENTS DURING THE TREATMENT - Al-Kazzaz, Fatin (Iraqi Journal of Science, 2024)
Ceruloplasmin oxidase (CP) activity, Copper concentration (Cu) and renal function was measured in sera of 87 patients with blood cancer (leukemia and multiple myeloma) ,34 patients with acute myeloblastic leukemia (AML),20 patients with acute lympholastic leukemia(ALL),13 patients with chronic myeloblastic leukemia (CML), 20 patients with multiple myeloma aged (5-62) years. In addition to 87 healthy individuals of match age and sex were utilized as control throughout this study.The first part of this study was devoted to measure of CP activities in sera of control and patients group before and after the first course of chemotherapy treatment (about 6 weeks). It was found that CP activities significantly higher than control groups (P<0.05) while the levels before chemotherapy were significantly higher than that after chemotherapy (P<0.05).Mean of sera CP levels of patients who passed away were higher than other patients.The second part of this study dealt with follow the changes in some biochemical parameters including blood creatinine (Cr), blood urea (U), uric acid (U.A) and copper (Cu) concentrations to evaluate the renal function as a complication in the studied patients.The results indicated the following:--The levels of U.A and Cu in sera of patients pre and post chemotherapy were significant more (P<0.05) than that of control group, while their levels before chemotherapy were significantly higher (P<0.05) than that after chemotherapy.-Blood urea U and Cr levels in sera of patients pre and post chemotherapy were insignificant more (P>0.05) than that of control group, the levels of both parameters before chemotherapy were significantly higher (P<0.05) than that after chemotherapy.To check if there is a relationship between CP activity with all of the above parameters before taking any dose of chemotherapy A-significant-positive-correlation was found between CP and U.A (r>0.5) while a non-significant positive correlation between CP and Cr, U (r<0.35).Conclusion of over all results in the present study enable the one to use serum CP, Cu and U.A rather than U and Cr as a biochemical marker to aid in the prognosis the blood cancer throughout treatment. Another conclusion is patients with blood cancer should evaluate their renal function through out taking their chemotherapy (especially first does) by measuring CP, Cu and U.A in their sera.